Transparent semiconducting oxides : bulk crystal growth and fundamental properties - Galazka, Zbigniew ([Place of publication not identified] : Jenny Stanford Publishing, 2020)
This book presents a collection of a number of transparent semiconducting oxides (TSOs) that were grown as bulk single crystals using diverse growth techniques and discusses the fundamental properties gathered directly from the bulk crystals. Properties of bulk crystals are closer to the intrinsic properties of an "ideal" compound due to much lower defect density that significantly affects the electrical, optical, magnetic, mechanical, and thermal properties. Combinations of various bulk single crystals along with their properties show great promise in practical device functionality and fabrication. The book explores the particularities of TSOs from a thermodynamic point of view and the technical approaches to obtain bulk crystals. It focuses on experimental results and is accompanied by theoretical results such as band structure and native defects. It incorporates advances of the TSOs that are or will be under intensive research as a result of material availability and unique properties of materials.
"Jenny Stanford Publishing"
OCLC-licensed vendor bibliographic record.
Keywords: Metal oxide semiconductors; Crystal growth; SCIENCE / Physics; TECHNOLOGY / Material Science; SCIENCE / Chemistry / Physical & Theoretical